Molly Learns a Lesson : A School Story - Tripp, Valerie, 1951-; Payne, C. F. (Madison, Wis. : Pleasant Co., 1986)
During World War II, nine-year-old Molly and her friends work on projects to aid the war effort.
During World War II, nine-year-old Molly goes to school and with her friends tries to aid the war effort.
Keywords: Schools -- Fiction; World War, 1939-1945 -- Fiction -- United States; School stories